The Differences of Pain Characteristics Among Post-Surgery Clients with General and Regional Anesthesia - Andi Eka Pranata; Feri Ekaprasetia (NurseLine Journal, 2021)
Background: Surgery is one of the medical options for improving health. Surgery will break the main chain that causes health problems. Patients undergoing surgery will receive anesthetic management to relieve pain sensations. Pain sensations will be felt again after the period of anesthesia gradually disappears. Post-surgery clients will feel pain that varies widely. Purpose: This study aims to determine differences in the characteristics of postoperative client pain with general anesthesia and regional anesthesia. Methods: The method used was observational in postoperative clients with a cross-sectional design. Pain characteristics were observed after 4 hours postoperatively. Observation of pain used a pain characteristic observation sheet with observation items including pain intensity, pain onset, pain quality, and pain coping pattern. Observations were made on 30 postoperative clients with general anesthesia and 30 postoperative clients with regional anesthesia. The pain characteristics of the two groups after surgery were compared and the differences were seen. Result: The results of the study generally showed that the characteristcis of postoperative client pain with regional anesthesia (mean score = 18.1) were heavier than clients who received general anesthesia (mean score = 17.5). The results of the Mann Whitney test showed that the value of p = 0.000 (pain scale), p = 0.017 (pain time range), 0.000 (pain onset), p = 0.018 (pain intensity), p = 0.000 (pain depth), p = 0.000 (coping pattern). Conclusion: There are differences in pain characteristics between postoperative clients with general anesthesia and regional anesthesia on the aspects of pain scale, pain onset, the intensity of pain, depth of pain, and coping patterns of pain. The length of time of surgery and the level of depth of the surgical incision have a very significant effect on the characteristics of postoperative pain.